Gender and Its Role for Islamic Entrepreneurship Implementation - Rahmawati, Rahmawati (MEC-J (Management and Economics Journal), 2020)
Nowadays, Islamic entrepreneurship is an important breakthrough considering that many business people ignore moral value because they are lulled by temporary world wealth. This study is gives some insight how gender with the role in Islamic entrepreneurship implementation has differences between man and women. This study used a narrative approach with the type of qualitative research. The data collection method used deep interview using model that has been developed by Hoque et al, which is formed in four key performance namely knowledge, social welfare, customer orientation, fear in Allah. Result of the study indicated that knowledge and customer orientation there are differences between man and women, but social welfare and fear in Allah have the same point of view.Â  Islam has an entrepreneurship view with the prominent characteristic. These salient qualities presuppose a separate spectrum to see that Islamic entrepreneurship is a business implementation that is guided by islam and combines with superior science.